2015
DOI: 10.3892/or.2015.4328
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of quiescent lung adenocarcinoma CD8+ T cells by MUC1-8-mer peptide-T2 cell-β2 microglobulin complexes

Abstract: Adoptive immunotherapy requires the isolation of CD8+ T cells specific for tumor-associated antigens, their expansion in vitro and their transfusion to the patient to mediate a therapeutic effect. MUC1 is an important adenocarcinoma antigen immunogenic for T cells. The MUC1-derived SAPDTRPA (MUC1-8-mer) peptide is a potent epitope recognized by CD8+ T cells in murine models. Likewise, the T2 cell line has been used as an antigen-presenting cell to activate CD8+ T cells, but so far MUC1 has not been assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…6). Reports have demonstrated that activation of cytotoxic T cell responses is essential for tumor cell elimination and the adoptive immunotherapy requires isolation and expansion of speci c CD8 + T cells [59,60]. Consequently, prominent and distinct associations have been To gain more insights into the functional roles of the immune-related lncRNAs, GO and pathway enrichment analyses performed in this study revealed that most of the signi cant items for each enrichment analysis were directly related to immune response (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…6). Reports have demonstrated that activation of cytotoxic T cell responses is essential for tumor cell elimination and the adoptive immunotherapy requires isolation and expansion of speci c CD8 + T cells [59,60]. Consequently, prominent and distinct associations have been To gain more insights into the functional roles of the immune-related lncRNAs, GO and pathway enrichment analyses performed in this study revealed that most of the signi cant items for each enrichment analysis were directly related to immune response (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Then, cells (6x10 5 ) were incubated with 80 μg of either Ag85Bp (199-207) target peptide and Esat-6p (82-90) as non-target. Twenty μg/ml of β2m (Sigma) was added according to ( 29 ). Cells were incubated for 8 h at 37°C in 5% CO 2 atmosphere, after that cells were washed twice with PBS and incubated with 10 μg of sdAb 2C ON at 4°C in agitation, and then washed 2 times, with PBS, following by incubation with anti-c-Myc Ab (Santa Cruz-/Europe) (1/100) for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%